Lead halide hybrid perovskite solar cell taking lanthanide metal-Salen complex interface layer as free radical scavenger
By using the lanthanide metal-Salen complex as the interface layer in perovskite solar cells, the impact of O2·-on on the photovoltaic performance of perovskite solar cells is solved, and the effect of improving photovoltaic performance and stability is achieved.
Patent Information
- Application Number
- CN202411842264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The impact of O2-formed by O2 under light conditions on photovoltaic performance has not been effectively resolved, resulting in perovskite film degradation and low photovoltaic performance.
The lanthanide metal-Salen complex is used as the interface layer and is prepared by spin coating method. It is used in perovskite solar cells. It has oxidation resistance and can remove O2·- produced by O2, and binds to the perovskite surface defects through uncoordinated -C=N- and O to passivate the defects.
It improves the photovoltaic performance and stability of perovskite solar cells, enhances the antioxidant ability of perovskite films, extends the carrier life, and improves the photoelectric conversion efficiency and environmental stability.
Smart Images

Figure CN119767928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectric materials and devices, in particular to a lead halide hybrid perovskite solar cell using a lanthanide metal-Salen complex interface layer as a free radical scavenger. Background Art
[0002] Perovskite solar cells have attracted widespread attention due to their advantages such as solution processing, low cost and high photovoltaic performance. At present, the highest certified photoelectric conversion efficiency of perovskite solar cells has reached 26.7%, but there is still a gap with the Shockley-Queisser theoretical limit efficiency. This is because there are a large number of defects on the surface of the perovskite film prepared by the solution method, such as under-coordinated ion defects, vacancy defects and grain boundary defects. These defects will form recombination sites for photogenerated carriers and hinder carrier transport, resulting in low photoelectric conversion efficiency of perovskite solar cells. In addition, the stability of perovskite films is also an important factor affecting the photovoltaic performance of perovskite solar cells. Many studies have shown that the stability of perovskite films with O2 ·- The reaction will accelerate the degradation of perovskite and deteriorate the stability of perovskite solar cells. For example, the literature "Fast oxygen diffusion and iodide defects mediate oxygen-induced degradation of perovskite solar cells" [1] It was found that perovskite films exposed to air and light would form O2 ·- , which leads to the degradation of perovskite film and affects the photovoltaic performance of perovskite solar cells. Therefore, it is urgent to find a method that can eliminate O2 ·- , and can passivate substances with surface defects in perovskite films, thereby improving the photovoltaic performance of perovskite solar cells.
[0003] Organic small molecules or polymers are usually passivators on the surface of perovskite films. On the one hand, small molecules or polymers can interact with perovskite to reduce surface defects of perovskite films. On the other hand, hydrophobic small molecules or polymers can prevent water from entering the perovskite. [2]In the study, a fluorinated conjugated polymer 3,4-difluorothiophene (PTzNDI-2FT) was synthesized and used as the interface layer of perovskite / Spiro-OMeTAD. In addition to improving the hydrophobicity of the perovskite film, the carbonyl group in PTzNDI-2FT can bind to the uncoordinated Pb in the perovskite. 2+ The interface-modified perovskite solar cells achieved a photoelectric conversion efficiency of 23.2% and showed high environmental and thermal stability. [3] In the paper, a multifunctional polymethyl methacrylate-co-acrylamide polymer (PMMA-AM) was designed as the interface layer of perovskite / Spiro-OMeTAD. The ester and amide groups in PMMA-AM can not only bind to the under-coordinated Pb 2+ Interaction, and amide can also interact with I - Hydrogen bond formation inhibits I - Migration, inhibiting the formation of vacancy defects. After interface modification, the open circuit voltage of the device was significantly increased from 1.12V to 1.22V and a photoelectric conversion efficiency of 23.24% was obtained. In addition, using a 2D perovskite layer to modify the 3D perovskite surface and passivate the surface defects of the perovskite film is also an effective strategy to improve the photoelectric conversion efficiency and stability of perovskite solar cells. [4] Guanidine bromide was selected as the interface layer between perovskite and hole transport layer, and it was found that guanidine bromide could induce recrystallization of perovskite film to form two-dimensional perovskite, reducing the surface defects of perovskite film. The photoelectric conversion efficiency of perovskite solar cells after interface modification increased from 15.9% to 19.3% and showed excellent environmental stability. Although small molecules or polymers and 2D perovskite layer modification of 3D perovskite surface can improve the photovoltaic performance and stability of perovskite solar cells, it does not solve the problem of O2 formed under light conditions. ·- Effects on the photovoltaic performance of perovskite solar cells.
[0004] References
[0005] 1.AristidouN,Eames C,Sanchez-Molina I,et al.Fast oxygen diffusion andiodide defects mediateoxygen-induced degradation of perovskite solar cells[J].Nature communications,2017,8(1):15218.
[0006] 2.Li Y,Lim EL,Xie H,et al.Hydrophobic fluorinated conjugatedpolymeras amultifunctional interlayer for high-performance perovskite solar cells[J].ACS Photonics,2021,8(11):3185-3192.3.Zhang B,Chen C,Wang X,et al.Amultifunctional polymer as an interfacial layer for efficient and stable perovskite solar cells[J]. Angewandte Chemie International Edition, 2023, 62(2):e202213478.
[0007] 4. Huang Y, Li Y, Lim EL, et al. Stable layered 2D perovskite solar cells with an efficiency of over 19% via multifunctional interfacial engineering [J]. Journal of the American Chemical Society, 2021, 143(10): 3911-3917. Summary of the invention
[0008] Based on the above problems existing in the prior art, the present invention provides a lead halide hybrid perovskite solar cell using a lanthanide metal-Salen (Ln-Salen) complex interface layer as a free radical scavenger to improve the photovoltaic performance and stability of the perovskite solar cell.
[0009] In order to achieve the above object, the present invention adopts the following technical scheme:
[0010] The present invention provides a lead halide hybrid perovskite solar cell using a lanthanide metal-Salen complex interface layer as a free radical scavenger. The lead halide hybrid perovskite solar cell comprises a substrate layer, a transparent conductive metal oxide layer, an electron transport layer, a perovskite layer, a Ln-Salen complex interface layer, a hole transport layer, and a metal electrode layer.
[0011] Furthermore, the Ln-Salen complex is one of [Sm(Salen)(NO3)3], [Eu(Salen)(NO3)3] and [Dy(Salen)(NO3)3], wherein Salen is bis(3-methoxysalicylene)-3-oxapentane-1,5-diamine. The Ln-Salen complex has antioxidant properties and can remove O2 produced by O2 · - .
[0012] Furthermore, the Ln-Salen complex interface layer is prepared by spin coating, and the concentration of the spin coating precursor solution (the complex is added to the solvent to form the required precursor solution) is 0.01-5 mg / mL, and the solvent is one or more of toluene, chlorobenzene, methanol, ethanol, and isopropanol.
[0013] Furthermore, the substrate layer is glass, quartz, flexible polyethylene terephthalate or flexible polyethylene naphthalate.
[0014] Furthermore, the transparent conductive metal oxide layer is fluorine-doped tin oxide or indium-doped tin oxide.
[0015] Furthermore, the electron transport layer is tin oxide, titanium oxide or zinc oxide.
[0016] Furthermore, the perovskite layer is Cs x (FA 1-y MA y ) 1-x Pb(I z Br 1-z )3, where 0≤x≤1, 0≤y≤1, 0≤z≤1.
[0017] Furthermore, the hole transport layer is 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene.
[0018] Furthermore, the metal electrode layer is a gold electrode or a silver electrode.
[0019] The beneficial effects of the present invention are embodied in:
[0020] Ln-Salen complex is a passivating agent with antioxidant and coordination ability. It is used in perovskite solar cells as the interface layer on the upper surface of the perovskite layer: on the one hand, the uncoordinated -C=N- and O in the Ln-Salen complex can react with the undercoordinated Pb 2+ Ion binding passivates surface defects; on the other hand, the Ln-Salen complex has antioxidant properties and can remove O2 produced by O2 ·- , avoid O2 · - It reacts with perovskite to inhibit the degradation of the perovskite layer, thereby improving the stability of the perovskite film. The photovoltaic performance and stability of the perovskite solar cell prepared by the Ln-Salen complex of the present invention are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the structure of the lead halide hybrid perovskite solar cell of the present invention and a schematic diagram of the interface passivation mechanism of the Ln-Salen complex;
[0022] Figure 2 is the JV curve of the lead halide hybrid perovskite solar cell prepared in Example 1;
[0023] Figure 3 is the JV curve of the lead halide hybrid perovskite solar cell prepared in Example 2;
[0024] Figure 4 is the JV curve of the lead halide hybrid perovskite solar cell prepared in Example 3;
[0025] Figure 5 The light stability of the lead halide hybrid perovskite solar cells prepared in Example 4 and Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent claims of the present invention.
[0027] Example 1
[0028] This embodiment provides a lead halide hybrid perovskite solar cell using an interface layer of a [Eu(Salen)(NO3)3] complex as a free radical scavenger, and the preparation steps are as follows:
[0029] (1) Etching and cleaning FTO conductive glass: After etching the FTO conductive glass with zinc powder and hydrochloric acid, the FTO conductive glass is ultrasonically cleaned with detergent, anhydrous ethanol, acetone and deionized water in sequence, and finally dried with nitrogen for later use.
[0030] (2) Preparation of electron transport layer: A SnO2 aqueous solution (the mass ratio of SnO2 to H2O is 1:4.2) was spin-coated on the FTO conductive glass at a speed of 3000 rpm for 30 s. After spin coating, the glass was annealed at 200°C for 1 h to form an electron transport layer.
[0031] (3) Preparation of perovskite layer: 44.5 mg MAI, 192.6 mg FAI, 677.7 mg PbI2, and 20.26 mg MACl were weighed and dissolved in a mixed solvent of 1 mL DMF and DMSO, where the volume ratio of DMF to DMSO was 8:1, to obtain a perovskite precursor solution, which was spin-coated on a FTO / SnO2 substrate. The first step was set to a speed of 1000 rpm for 10 s, and the second step was set to a speed of 5000 rpm for 50 s. 10 to 30 s before the end of the second step, 200 μL of toluene antisolvent was added dropwise. After spin coating, the solution was annealed at 150°C for 0.5 h to form a perovskite layer.
[0032] (4) Preparation of the complex interface layer:
[0033] The preparation method of [Eu(Salen)(NO3)3] refers to the method in the reference "Tang X, Shi X, Xu Y, et al. Synthesis, Crystal Structure, Fluorescent and Antioxidation Properties of Cerium(III)andEuropium(III) Complexes with Bis(3-methoxysalicylidene)-3-oxapentane-1,5-diamine[J]. Zeitschrift für anorganische und allgemeineChemie, 2017, 643(5): 379-386." The corresponding sample in the reference is [Eu(Bod)(NO3)3].
[0034] [Eu(Salen)(NO3)3] was added to toluene to prepare a [Eu(Salen)(NO3)3] solution with a concentration of 0.15 mg / mL, which was spin-coated on the perovskite film at a speed of 3000 rpm and a time of 30 s. After spin coating, it was annealed at 50°C for 12 min to form a complex interface layer.
[0035] (5) Preparation of hole transport layer: A hole transport layer solution (containing 72.3 mg of 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene, 28.8 μL of 4-tert-butylpyridine and 17.5 μL of bis(trifluoromethanesulfonyl)imide lithium salt (520 mg / mL) acetonitrile solution, 1 mL of chlorobenzene) was spin-coated on the complex interface layer at a rotation speed of 4000 rpm for 30 s to form a hole transport layer.
[0036] (6) Preparation of metal electrode layer: The sample is placed in a vacuum evaporation device and a 60 nm thick Au electrode is evaporated through a thermal evaporation process to complete the preparation of the perovskite solar cell.
[0037] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery is tested under the conditions of Figure 2 As shown, it can be seen that the sample obtained an open circuit voltage of 1.05V and a current of 24.20mAcm -2 The short-circuit current density, fill factor of 78.1%, and photoelectric conversion efficiency of 19.76% are achieved.
[0038] Example 2
[0039] This embodiment provides a lead halide hybrid perovskite solar cell using a [Sm(Salen)(NO3)3] complex interface layer as a free radical scavenger, and the preparation steps are as follows:
[0040] (1) Etching and cleaning FTO conductive glass: the same as in Example 1.
[0041] (2) Preparation of electron transport layer: The cleaned FTO conductive glass was placed in a 0.04M TiCl4 aqueous solution and kept in an oven at 70°C for 0.5 h. The FTO conductive glass was rinsed with deionized water, dried with nitrogen, and kept on a heating table at 200°C for 1 h to deposit a TiO2 thin film.
[0042] (3) Preparation of perovskite layer: 10.9 mg CsI, 11.97 mg MAI, 221.5 mg FAI, 677.7 mg PbI2, and 20.26 mg MACl were weighed and dissolved in a mixed solvent of 1 mL DMF and DMSO, wherein the volume ratio of DMF to DMSO was 8:1, to obtain a perovskite precursor solution, which was spin-coated on a FTO / TiO2 substrate. The first step was set to a speed of 1000 rpm for 10 s, and the second step was set to a speed of 5000 rpm for 50 s. 10 to 30 s before the end of the second step, 200 mL of toluene antisolvent was added dropwise. After spin coating, the solution was annealed at 150°C for 0.5 h to form a perovskite layer.
[0043] (4) Preparation of the complex interface layer:
[0044] The preparation method of [Sm(Salen)(NO3)3] refers to the method in the reference "Shi X, Mao S, Shen K, et al. Synthesis, crystal structure, antioxidant and fluorescence of two lanthanide complexes with a noncyclic polyether Schiffbase ligand[J]. Journal of Coordination Chemistry, 2017, 70(12): 2015-2028." The corresponding sample in the reference is [Sm(Bod)(NO3)3].
[0045] [Sm(Salen)(NO3)3] was added to toluene to prepare a [Sm(Salen)(NO3)3] solution with a concentration of 0.50 mg / mL, which was spin-coated on the perovskite film at a rotation speed of 3000 rpm and a time of 30 s. After spin coating, it was annealed at 90°C for 6 min to form a complex interface layer.
[0046] (5) Preparation of hole transport layer: same as in Example 1.
[0047] (6) Preparation of metal electrode layer: same as in Example 1.
[0048] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery is tested under the conditions of Figure 3 As shown, it can be seen that the sample obtained an open circuit voltage of 1.08V and a current of 24.42mAcm -2 The short-circuit current density, fill factor of 80.6%, and photoelectric conversion efficiency of 21.36% are achieved.
[0049] Example 3
[0050] This embodiment provides a lead halide hybrid perovskite solar cell using a [Dy(Salen)(NO3)3] complex interface layer as a free radical scavenger, and the preparation steps are as follows:
[0051] (1) Etching and cleaning FTO conductive glass: the same as in Example 1.
[0052] (2) Preparation of electron transport layer: same as in Example 1.
[0053] (3) Preparation of perovskite layer: 222.5 mg MAI, 677.7 mg PbI2, and 10.26 mg MACl were weighed and dissolved in a mixed solvent of 1 mL DMF and DMSO, where the volume ratio of DMF to DMSO was 8:1, to obtain a perovskite precursor solution, which was spin-coated on a FTO / SnO2 substrate. The first step was set to a speed of 1000 rpm for 10 s, and the second step was set to a speed of 5000 rpm for 50 s. 10 to 30 s before the end of the second step, 200 mL of toluene antisolvent was added dropwise. After spin coating, the solution was annealed at 100°C for 0.5 h to form a perovskite layer.
[0054] (4) Preparation of the complex interface layer:
[0055] The preparation method of [Dy(Salen)(NO3)3] refers to the method in the reference "Li CF, Xu YL, Bai YC, et al. Synthesis, Crystal Structure, Antioxidation, and Luminescence of a Mononuclear Dysprosium(III) Complex Based on the Bis(3-Methoxysalicylidene)-3-Oxapentane-1,5-DiamineLigand[J]. Chemical Engineering, 2017, 43(1):54-62." The corresponding sample in the reference is [Dy(Bod)(NO3)3].
[0056] [Dy(Salen)(NO3)3] was added to toluene to prepare a [Dy(Salen)(NO3)3] solution with a concentration of 1.0 mg / mL, which was spin-coated on the perovskite film at a speed of 3000 rpm and a time of 30 s. After spin coating, it was annealed at 60°C for 24 min to form a complex interface layer.
[0057] (5) Preparation of hole transport layer: same as in Example 1.
[0058] (6) Preparation of metal electrode layer: same as in Example 1.
[0059] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery is tested under the conditions of Figure 4 As shown, it can be seen that the sample obtained an open circuit voltage of 1.02V and a current of 23.50mAcm -2 The short-circuit current density, fill factor of 75.5%, and photoelectric conversion efficiency of 18.10% are achieved.
[0060] Example 4
[0061] This embodiment provides a lead halide hybrid perovskite solar cell using a [Sm(Salen)(NO3)3] complex interface layer as a free radical scavenger, and the preparation steps are as follows:
[0062] (1) Etching and cleaning FTO conductive glass: the same as in Example 1.
[0063] (2) Preparation of electron transport layer: same as in Example 1.
[0064] (3) Preparation of perovskite layer: same as in Example 1.
[0065] (4) Preparation of the complex interface layer: [Sm(Salen)(NO3)3] was added to toluene to prepare a [Sm(Salen)(NO3)3] solution with a concentration of 0.15 mg / mL, which was spin-coated on the perovskite film at a speed of 3000 rpm for 30 s. After spin coating, the film was annealed at 50°C for 12 min to form a complex interface layer.
[0066] (5) Preparation of hole transport layer: same as in Example 1.
[0067] (6) Preparation of metal electrode layer: same as in Example 1.
[0068] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery was tested under the conditions of 1.07V open circuit voltage and 24.15mAcm -2 The short-circuit current density, fill factor of 81.9%, and photoelectric conversion efficiency of 21.10% are achieved. Figure 5 This is the light stability of the battery tested under AM1.5 conditions. It can be seen that the light stability of the sample is significantly higher than that of comparative example 1.
[0069] Example 5
[0070] This embodiment provides a lead halide hybrid perovskite solar cell using a [Dy(Salen)(NO3)3] complex interface layer as a free radical scavenger, and the preparation steps are as follows:
[0071] (1) Etching and cleaning FTO conductive glass: the same as in Example 1.
[0072] (2) Preparation of electron transport layer: same as in Example 1.
[0073] (3) Preparation of perovskite layer: same as in Example 1.
[0074] (4) Preparation of the complex interface layer: [Dy(Salen)(NO3)3] was added to toluene to prepare a [Dy(Salen)(NO3)3] solution with a concentration of 0.15 mg / mL, which was spin-coated on the perovskite film at a speed of 3000 rpm for 30 s. After spin coating, the film was annealed at 50°C for 12 min to form a complex interface layer.
[0075] (5) Preparation of hole transport layer: same as in Example 1.
[0076] (6) Preparation of metal electrode layer: same as in Example 1.
[0077] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery was tested under the conditions of 1.04 V open circuit voltage and 24.16 mA cm -2 The short-circuit current density, fill factor of 80.8%, and photoelectric conversion efficiency of 20.40% are achieved.
[0078] Comparative Example 1
[0079] In this comparative example, a lead halide hybrid perovskite solar cell was prepared in the same manner as in Example 1, except that no complex interface layer was provided between the perovskite layer and the hole transport layer.
[0080] At AM1.5, the effective area of the active layer is 0.04cm -2 The battery was tested under the conditions of , and the sample obtained an open circuit voltage of 0.99V and a current of 24.11mA cm -2 The short-circuit current density, fill factor of 76.8%, and photoelectric conversion efficiency of 18.29% are achieved.
[0081] The above description is only an exemplary embodiment of the present invention and does not limit the present invention in any way. Any modification and equivalent changes made according to the method of the present invention still fall within the scope of protection of the present invention.
Claims
1. A lead halide hybrid perovskite solar cell using a lanthanide metal-Salen complex interface layer as a free radical scavenger, the lead halide hybrid perovskite solar cell comprising a substrate layer, a transparent conductive metal oxide layer, an electron transport layer, a perovskite layer, a hole transport layer, and a metal electrode layer, characterized in that: A Ln-Salen complex interface layer is also provided between the perovskite layer and the hole transport layer.
2. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The Ln-Salen complex is one of [Sm(Salen)(NO3)3], [Eu(Salen)(NO3)3] and [Dy(Salen)(NO3)3], wherein Salen is bis(3-methoxysalicylene)-3-oxapentane-1,5-diamine.
3. The lead halide hybrid perovskite solar cell according to claim 1 or 2, characterized in that: The Ln-Salen complex interface layer has antioxidant properties and can remove O2 produced by · - .
4. The lead halide hybrid perovskite solar cell according to claim 1 or 2, characterized in that: The Ln-Salen complex interface layer is prepared by spin coating, the concentration of the spin coating precursor solution used is 0.01-5 mg / mL, and the solvent is one or more of toluene, chlorobenzene, methanol, ethanol, and isopropanol.
5. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The substrate layer is glass, quartz, flexible polyethylene terephthalate or flexible polyethylene naphthalate.
6. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The transparent conductive metal oxide layer is fluorine-doped tin oxide or indium-doped tin oxide.
7. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The electron transport layer is tin oxide, titanium oxide or zinc oxide.
8. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The perovskite layer is Cs x (FA 1-y MA y ) 1-x Pb(I z Br 1-z )3, where 0≤x≤1, 0≤y≤1, 0≤z≤1.
9. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene.
10. The lead halide hybrid perovskite solar cell according to claim 1, characterized in that: The metal electrode layer is a gold electrode or a silver electrode.
Citation Information
Patent Citations
Perovskite solar cell based on high-transparent conductive LaNiO<3> hole transporting layer, and preparation method thereof
CN108400249A
Perovskite solar cell
CN114203911A
Perovskite solar cell taking lead-halogen adduct as interface passivation layer and preparation method thereof
CN115101670A
Gas auto supply system of gas cylinder and method of controlling the same
KR102345573B1